Non-specific electrocardiographic ST-T abnormalities predict mortality in patients on peritoneal dialysis - Zhan, Xiaojiang; Zeng, Chuanfei; He, Jiajing; Wang, Menghui; Xiao, Jun (Frontiers in Cardiovascular Medicine, 2022)
Background This study aimed to evaluate the predictive value of non-specific ST-segment and/or T-wave abnormalities in electrocardiography (ECG) for all-cause and cardiovascular mortality (CVM) in peritoneal dialysis (PD) patients. Methods All patients who started PD between November 1, 2005, and February 28, 2017, at the First Affiliated Hospital of Nanchang University were enrolled. The primary outcomes were all-cause mortality and CVM. The Kaplan–Meier method and a log-rank test were used for the survival analysis. Multivariate Cox proportional hazards models were used to investigate the risk factors for all-cause mortality and CVM. Results A total of 724 eligible PD patients were enrolled, including 401 (55.4%) men. In total, 153 (21.1%) patients died during a mean follow-up period of 27 (interquartile range, 13–41) months, and cardiovascular death was responsible for 84 of these deaths. The patients with non-specific ST-T abnormalities (NSSTTAs) had lower overall and cardiovascular survival rates compared to those free from any ECG abnormalities. According to the multivariate Cox proportional hazards models, (NSSTTAs) are independent risk factors for all-cause mortality and CVM, the hazard ratios are 1.81 (95% confidence interval, 1.11–2.95; p = 0.017) and 2.86 (95% confidence interval, 1.52–5.37; p = 0.001), respectively. Conclusion Non-specific ST-T abnormalities can serve as risk markers of all-cause and CVM in PD patients.